Personalized medicine in Europe: not yet personal enough? - Antonello Di Paolo; François Sarkozy; Bettina Ryll; Uwe Siebert (BMC, 2017)
Abstract Background Personalized medicine has the potential to allow patients to receive drugs specific to their individual disease, and to increase the efficiency of the healthcare system. There is currently no comprehensive overview of personalized medicine, and this research aims to provide an overview of the concept and definition of personalized medicine in nine European countries. Methods A targeted literature review of selected health databases and grey literature was conducted to collate information regarding the definition, process, use, funding, impact and challenges associated with personalized medicine. In-depth qualitative interviews were carried out with experts with health technology assessment, clinical provisioning, payer, academic, economic and industry experience, and with patient organizations. Results We identified a wide range of definitions of personalized medicine, with most studies referring to the use of diagnostics and individual biological information such as genetics and biomarkers. Few studies mentioned patients' needs, beliefs, behaviour, values, wishes, utilities, environment and circumstances, and there was little evidence in the literature for formal incorporation of patient preferences into the evaluation of new medicines. Most interviewees described approaches to stratification and segmentation of patients based on genetic markers or diagnostics, and few mentioned health-related quality of life. Conclusions The published literature on personalized medicine is predominantly focused on patient stratification according to individual biological information. Although these approaches are important, incorporation of environmental factors and patients' preferences in decision making is also needed. In future, personalized medicine should move from treating diseases to managing patients, taking into account all individual factors.